2021
DOI: 10.1172/jci.insight.148028
|View full text |Cite
|
Sign up to set email alerts
|

PLA2G4A promotes right-sided colorectal cancer progression by inducing CD39+γδ Treg polarization

Abstract: γδ T cell is a promising candidate cell in tumor immunotherapy. However, γδ T cells polarized to CD39 + γδ Tregs upon colorectal cancer (CRC) induction and the underlying mechanism remains unclear. Here, we discovered that the frequency of CD39 + γδ Tregs, which positively correlated with poor prognosis, was significantly higher in right-sided CRC (RSCRC) than in the left-sided CRC (LSCRC). Interestingly, CD39 + γδ Tregs from RSCRC showed stronger immunosuppressive phenotype and function than LSCRC. Further, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Translationally, targeting BGN represents a possible strategy to reorient TAMs toward the antitumor M1 phenotype. Treg cells are another vital group of immunosuppressive cells that mediate immune tolerance, inhibition of Tregs by targeting pivotal molecules could reverse tumor immunosuppression (52)(53)(54). In our present study, BGNmediated immunosuppression may also involve Treg cells, which are functionally categorized into nTregs and iTregs (55).…”
Section: Discussionmentioning
confidence: 65%
“…Translationally, targeting BGN represents a possible strategy to reorient TAMs toward the antitumor M1 phenotype. Treg cells are another vital group of immunosuppressive cells that mediate immune tolerance, inhibition of Tregs by targeting pivotal molecules could reverse tumor immunosuppression (52)(53)(54). In our present study, BGNmediated immunosuppression may also involve Treg cells, which are functionally categorized into nTregs and iTregs (55).…”
Section: Discussionmentioning
confidence: 65%
“…The cytoplasmic phospholipase A2-α (cPLA2α) encoded by the PLA2G4A gene acts as an upstream regulator of the eicosanoid signaling pathway by providing intracellular AA ( Bazhan and Khaniani, 2018 ). Studies have shown that the PLA2G4A gene can be used as a biomarker in various diseases such as gastric cancer ( Bazhan and Khaniani, 2018 ), acute myeloid leukemia ( Hassan et al, 2021 ; Lai et al, 2021 ), cholangiocarcinoma ( Sun et al, 2019 ), and colorectal cancer ( Zhan et al, 2021a ). PLA2G4A activates the colorectal cancer microenvironment to produce pro-cytokines IL-17A and adenosine, thereby establishing an effective immunosuppressive microenvironment and promoting immune evasion and tumor metastasis ( Zhan et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the PLA2G4A gene can be used as a biomarker in various diseases such as gastric cancer ( Bazhan and Khaniani, 2018 ), acute myeloid leukemia ( Hassan et al, 2021 ; Lai et al, 2021 ), cholangiocarcinoma ( Sun et al, 2019 ), and colorectal cancer ( Zhan et al, 2021a ). PLA2G4A activates the colorectal cancer microenvironment to produce pro-cytokines IL-17A and adenosine, thereby establishing an effective immunosuppressive microenvironment and promoting immune evasion and tumor metastasis ( Zhan et al, 2021b ). Trametinib inhibits the cell viability and signaling of organoids to a greater extent by inhibiting the expression of PLA2G4A ( Klotsman et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD39 + γδTregs are the predominant Treg subtype in human CRC. They act through adenosine-mediated pathways and have stronger immunosuppressive activity than CD4 + or CD8 + Tregs [ 60 ]. The Myeloid-derived suppressor cells (MDSC) can be attracted by the secretion of cytokines such as IL17A and GM-CSF, thus establishing an immunosuppressive network [ 61 ].…”
Section: Tme and Chemotherapy Obstaclesmentioning
confidence: 99%